2007
DOI: 10.1111/j.1600-0501.2007.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the survival and complication rates of all‐ceramic and metal–ceramic reconstructions after an observation period of at least 3 years. Part I: single crowns

Abstract: Based on the present systematic review, all-ceramic crowns, when used for anterior teeth, showed survival rates at 5 years comparable to those seen for metal-ceramic crowns. When used for posterior teeth, the survival rates at 5 years of densely sintered alumina crowns (94.9%) and reinforced glass-ceramic crowns (93.7%) were similar to those obtained for metal-ceramic crowns. Furthermore, lower survival rates of 90.4% and 84.4% can be expected for InCeram crowns and glass-ceramic crowns when utilized for premo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
314
2
38

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 392 publications
(369 citation statements)
references
References 27 publications
15
314
2
38
Order By: Relevance
“…For the statistical analysis the new data of the present review, encompassing the 33 studies was combined with the previous data of the 34 studies published in Pjetursson et al, 2007. Hence, the data included in the present analysis was published from 1990 until the end of 2013.…”
Section: Discussionmentioning
confidence: 99%
“…For the statistical analysis the new data of the present review, encompassing the 33 studies was combined with the previous data of the 34 studies published in Pjetursson et al, 2007. Hence, the data included in the present analysis was published from 1990 until the end of 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective clinical trial chipping was observed in 13% after three years [9] and 15% after 5 years [10]. These failure rates are significantly higher compared to metalceramic restorations [11,12]. A thermal incompatibility between framework and veneer is suggested to be one reason for chipping [7].…”
Section: Introductionmentioning
confidence: 99%
“…These types of bridges succeed, despite this dire prognosis, on those rare occasions when the root support is especially robust and the occlusal constraints are especially feeble 42,49,53,54 . In general, the participation of the canine in disoccluding the posterior teeth in lateral and protrusive excursions makes it necessary for the dentist include in the reconstruction to replace a missing canine all the teeth from the premolars on the ipsilateral side and at least the central incisor, and possibly the lateral incisor and canine on the contralateral side ( fig.…”
Section: -Replacing Missing Caninesmentioning
confidence: 99%